Вплив «Гуміліду» на показники білкового обміну та стан еритроцитопоезу кіз горьківської породи - Рибалка, Михайло Андрійович; Rybalka, M.; Степченко, Лілія Михайлівна; Stepchenko, L.; Шулешко, Олександр Олексійович; Shuleshko, O. O.; Shuleсhko, O. (Дніпропетровський ДАЕУ, 2016)
Наведено результати досліджень біохімічних та гематологічних показників крові кіз на тлі застосування біологічної активної добавки “Гумілід”. У результаті біохімічних досліджень у тварин дослідної групи було відмічено підвищення загального білка на 9,0%, збільшення рівня сечовини на 14,1%, зменшення рівня креатиніну на 35,4%, зменшення ліпопротеїдів на 11,1%. З морфологічного аналізу крові потрібно підкреслити здатність досліджуваної кормової добавки впливати на еритрон, що підтверджувалося в збільшені кількості еритроцитів на 8,8%, рівня гемоглобіну на 8,2%, гематокриту на 0,6%, кольорового показника на 2,3%. Many years of research from the action of natural food supplements “Humilid” on animals show the ability of stimulating erytropoeise, carbohydrate metabolism, lipid metabolism, enhance IgG synthesis and other blood proteins, which leads to increased resistance and qualities of animal production. The relevance of using biologically active supplements “Humilid” emphasizes its safety, low cost and hepato properties. An important factor is that this additive can cause physiological way that animals with food and water. Research conducted at Gorky breed goats under the conditions zoozony central recreation park named after TG Shevchenko. According to the principle analogues were formed control and experimental groups of 3 animals in each group. Animals experimental group for 30 days in addition to the basic feed ration asked together with water “Humilid” (5 mg of active ingredient per kg of body weight). Animals in both groups during the experiment were the same conditions of feeding and maintenance. Adding to the diets of dietary supplement “Humilid” affects the parameters characterizing homeostasis Gorky goat breed. In goats experimental group observed intensification of protein metabolism, manifested in increased by 14.1% urea and creatinine levels decrease by 35.4% compared with the control group. The increasing role creatine in bioenergy muscle tissue suggests reducing destructive processes in muscles, accompanied by a decrease in creatinine level in the blood of experimental goats. At the same time there is a growth of total protein at the end of the experiment at 9.0% compared with its beginning. The use of dietary supplements affect yerytron animals shown in the synthesis of hemoglobin increased by 8.2%. Marked increase adaptive capacity of the organism of experimental animals, shown to reduce weight loss in winter, indicating the possibility of using “Humilid” the adaptation of animals to extreme conditions.
Impact on indicators of “Humilid” on protein metabolism and the state of the erytropoeise gorky breed goats
Keywords: “Гумілід”; “Humilid”; кози; goats; біохімічні та гематологічні показники сироватки кров; biochemical and hematological blood parameters